2021
DOI: 10.5946/ce.2021.019
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Endoscopic Sleeve Gastroplasty as an Alternative to Laparoscopic Sleeve Gastrectomy

Abstract: Endoscopic sleeve gastroplasty (ESG) is a therapeutic endoscopic technique for reducing the size of the gastric reservoir in obese patients, using a full-thickness endoscopic suturing device. The effectiveness of ESG in weight loss is significantly greater than that of high-intensity diet and lifestyle therapy and lower than that of laparoscopic sleeve gastrectomy (LSG). The efficacy at 12 months after ESG in terms of percentage of total body weight loss and excess body weight loss was approximately 16% and 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…risk-free and acceptable as an LSG substitute. 16 Similarly, Fiorillo et al revealed in their findings that LSG may have a major negative impact on quality of life and aggravate gastrointestinal problems, such as GERD. ESG is a promising bariatric endoscopic treatment that is less intrusive and has shown to improve quality of life and comorbidities, which may make it more acceptable to patients earlier in their disease or when they are younger.…”
Section: Lsg Versus Esg; Evidence From Literaturementioning
confidence: 95%
“…risk-free and acceptable as an LSG substitute. 16 Similarly, Fiorillo et al revealed in their findings that LSG may have a major negative impact on quality of life and aggravate gastrointestinal problems, such as GERD. ESG is a promising bariatric endoscopic treatment that is less intrusive and has shown to improve quality of life and comorbidities, which may make it more acceptable to patients earlier in their disease or when they are younger.…”
Section: Lsg Versus Esg; Evidence From Literaturementioning
confidence: 95%
“…An expert consensus indicated that GERD is a contraindication to LSG [ 37 ]. The possible causes of LSG inducing GERD are low maximal distal contraction integral and low resting esophageal sphincter pressure [ 13 , 38 ]. Fayad et al showed how ESG and LSG affect GERD [ 32 ].…”
Section: Endoscopic Sleeve Gastroplastymentioning
confidence: 99%
“…EBMT reduces weight and ameliorates obesity-associated complications [ 12 , 13 ]. However, EBMTs can result in adverse events, including nausea, abdominal pain, and gastroesophageal reflux disease (GERD) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We aim to review the various EBMT techniques, focusing on non-balloon and non-gastroplasty devices, as the use of those devices is well described elsewhere in this issue of Clinical Endoscopy. 7,8 We will discuss the possible mechanisms of action, efficacy, and safety profiles of these EBMT methods.…”
Section: Introductionmentioning
confidence: 99%